2019
DOI: 10.1103/physrevmaterials.3.104409
|View full text |Cite
|
Sign up to set email alerts
|

Case study of bilayered spin- 12 square lattice compound VO(HCOO)2·(H2

Abstract: We present the synthesis and a detail investigation of structural and magnetic properties of polycrystalline [VO(HCOO)2·(H2O)] by means of x-ray diffraction, magnetic susceptibility, highfield magnetization, heat capacity, and electron spin resonance measurements. It crystallizes in a orthorhombic structure with space group P cca. It features distorted VO6 octahedra connected via HCOO linker (formate anions) forming a two-dimensional square lattice network with a bilayered structure. Analysis of magnetic susce… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
4
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
4

Relationship

2
2

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 56 publications
(49 reference statements)
0
4
0
Order By: Relevance
“…S1 within the Supplemental Material [43]. Similar procedures have been used previously and have shown to be efficient for estimating C ph in cases where heat-capacity data of nonmagnetic analog compounds are not available [44][45][46][47]. The fit is extrapolated down to low temperatures, and the magnetic specific heat dT .…”
Section: Methodsmentioning
confidence: 99%
“…S1 within the Supplemental Material [43]. Similar procedures have been used previously and have shown to be efficient for estimating C ph in cases where heat-capacity data of nonmagnetic analog compounds are not available [44][45][46][47]. The fit is extrapolated down to low temperatures, and the magnetic specific heat dT .…”
Section: Methodsmentioning
confidence: 99%
“…For estimating the C ph , the zero-field data were fitted by a polynomial function C ph (T ) = aT 3 + bT 5 + cT 7 above 10 K, where a, b, and c are appropriate constants [53]. Similar procedures have been adopted earlier and proven to be efficient in cases where heat capacity data of nonmagnetic analog compounds are unavailable [54][55][56][57]. The fit was extrapolated down to low temperatures, and C m was obtained by subtracting the fitted data from the experimental C p data.…”
Section: Methodsmentioning
confidence: 99%
“…Thus, this compound is another example of a quasi-2D non-frustrated system with J 1 /T N > 2.7, similar to the compounds tabulated in ref. [26].…”
Section: Magnetic Susceptibilitymentioning
confidence: 99%
“…Some of the recent studies have reported the signature of spin nematic phase in BaCdVO(PO 4 ) 2 [23][24][25]. A few metal-organic compounds based on V 4+ and Cu 2+ have also been studied in light of the 2D spin-1/2 Heisenberg model [26][27][28][29]. A series of Cubased quasi-2D organometallic magnets where Cu 2+ ions are bridged by pyrazine molecules are [Cu(HF 2 )(pyz) 2 ]X (X = BF − 4 , ClO − 4 , PF − 6 , SbF − 6 , and AsF − 6 ) [30] and [Cu(pyz) 2 ]X 2 (X = ClO − 4 and BF − 4 ) [31][32][33].…”
mentioning
confidence: 99%